The Effect of Profit Growth and Price Earnings Ratio on Stock Return in Property and Real Estate Companies Listed on the Indonesia Stock Exchange for the 2020-2022 Period - Azis, Muhammad; Anwar, Azwar; Yoshita, Rika (Jurusan Akuntansi Politeknik Negeri Ujung Pandang, 2024)
This research aims: (1) To analyze the effect of profit growth on stock returns in Property & Real Estate companies listed on the Indonesia Stock Exchange for the 2020-2022 period, (2) To analyze the influence of the Price Earnings Ratio on stock returns in Property & Real Estate companies listed on the Indonesia Stock Exchange 2020-2022, (3) To analyze the simultaneous influence of profit growth and Price Earnings Ratio variables on share returns in Property & Real Estate companies listed on the Indonesia Stock Exchange for the 2020-2022 period. The independent variables in this research are (1) Profit Growth, and (2) Price Earnings Ratio, while the dependent variable is Stock Return. The population of this research is all financial reports of Property & Real Estate Companies, while the research sample is the financial reports of Property & Real Estate Companies using a purpose sampling technique of 14 companies. Data collection is carried out using documentation. Data analysis was carried out using multiple linear regression analysis. The results of this research show that all independent variables influence the dependent variable significantly, both partially and simultaneously. The implications of this research provide empirical evidence that profit growth and stock prices in relation to profits influence stock returns or the profits obtained by investors from the funds invested in an investment. Thus, it is best for companies to maintain profits and profit growth in order to maintain company values.